Comparison of Changes in Center of Pressure and Time to Stabilization in Students with and without Hyperlordosis - Farideh Babakhani; Mohamadreza Hatefi; Mona Heydarian; Masod Barzegar (Islamic Azad University, Hamedan Branch, 2018)
Objective Considering the importance of balance in performing daily tasks and sports activities, it is necessary to examine the balance of the body from different angles. The aim of this study was to compare the changes in Center of Pressure (COP) and Time to Stabilization (TTS) in students with and without hyperlordosis.  Methods In this study, 30 female students of Tehran's middle school with a range of 14-15 years old who were selected by available sampling method were participated. Subjects' spinal curvature was evaluated by a flexible ruler. Which divided into two groups: 15 patients with hypereloidosis and 15 healthy subjects. To assess postural static stability in a static state, from open and closed eyes on the force plate (Ver 3.0.2 model from an Iranian scientist) was used. also to assess postural stability in the dynamic state, the landing stability test on the force plate device was used. Independent Sample T test statistics were used to analyze the data.  Results The results of the statistical test showed that there was no significant difference in the parameters of the center of pressure (COP) in two- position with open and closed eyes between the two groups of healthy and hyperlordosis (p>0.05). But the time to stabilization (TTS) between the two healthy groups and hyperlordosis was statistically significant (p<0.05). Conclusion The results of this study showed that the Spine Curvature Disorders (hyperlordosis) as a risk factor can distort the dynamic balance index (time to stabilization), But has no affect the static balance with both open eyes and closed eyes (center of pressure).